(untitled) (Movimenta (ISSN 1984-4298), 2023)
Objective: to analyze the motor performance of premature infants discharged from the Neonatal Intensive Care Unit (NICU) immediately after hospital discharge and verify associations with neonatal data (gestational age, birth weight, Apgar score), length of hospital stay, time after hospital discharge and corrected age on the day of assessment. Method: Cross-sectional observational study that included premature infants (GA<37 weeks) who were admitted to the NICU in three hospitals in a city in the interior of the state of São Paulo. 30 infants participated (GA 32±2 weeks), discharged from the NICU (27±26 days of hospitalization), with time at home post-hospital discharge of 35±21 days and corrected age of 41±4 weeks. Motor performance was assessed using the Test of Infant Motor Performance (TIMP) and General Movement Assessment (GMA). The analysis was performed using descriptive statistics (classification of motor performance by TIMP and GMA) and inferential statistics with Multiple Linear Regression to test the association between motor performance and predictor variables (neonatal data, length of hospital stay, time after discharge hospital and corrected age). Results: GMA was altered for age in 83% of infants (80% had poor motor repertoire). In the TIMP, all infants performed below expectations for their age (Z<-0.5 SD). Specifically, 10% showed medium-low motor performance, 53% suspected delayed performance and 37% atypical performance. The predictor variable "time after hospital discharge" was significant and included in the regression model. Time after hospital discharge predicted 33.3% of the variation in motor performance with an increase of 0.599 points in TIMP for each day at home. Conclusion: Premature infants discharged from the NICU showed impaired motor performance and was positively associated with time after hospital discharge.